Type II mode of JAK2 inhibition and destabilization are potential therapeutic approaches against the ruxolitinib resistance driven myeloproliferative neoplasms - Gorantla, Sivahari P.; Prince, Gerin; Osius, Jasmin; Dinesh, Dhurvas Chandrasekaran; Boddu, Vijay; Duyster, Justus; von Bubnoff, Nikolas (Frontiers in Oncology, 2024)
Background: Ruxolitinib has been approved by the US FDA for the treatment of myeloproliferative neoplasms such as polycythemia vera and primary myelofibrosis. Ruxolitinib will remain a main stay in the treatment of MPN patients due to its effective therapeutic benefits. However, there have been instances of ruxolitinib resistance in MPN patients. As JAK2 is a direct target of ruxolitinib, we generated ruxolitinib-resistant clones to find out the mechanism of resistance. Methods: Cell-based screening strategy was used to detect the ruxolitinib-resistant mutations in JAK2. The Sanger sequencing method was used to detect the point mutations in JAK2. Mutations were re-introduced using the site-directed mutagenesis method and stably expressed in Ba/F3 cells. Drug sensitivities against the JAK2 inhibitors were measured using an MTS-based assay. JAK2 and STAT5 activation levels and total proteins were measured using immunoblotting. Computational docking studies were performed using the Glide module of Schrodinger Maestro software. Results: In this study, we have recovered seven residues in the kinase domain of JAK2 that affect ruxolitinib sensitivity. All these mutations confer cross-resistance across the panel of JAK2 kinase inhibitors except JAK2-L983F. JAK2-L983F reduces the sensitivity towards ruxolitinib. However, it is sensitive towards fedratinib indicating that our screen identifies the drug-specific resistance profiles. All the ruxolitinib-resistant JAK2 variants displayed sensitivity towards type II JAK2 inhibitor CHZ-868. In this study, we also found that JAK1-L1010F (homologous JAK2-L983F) is highly resistant towards ruxolitinib suggesting the possibility of JAK1 escape mutations in JAK2-driven MPNs and JAK1 mutated ALL. Finally, our study also shows that HSP90 inhibitors are potent against ruxolitinib-resistant variants through the JAK2 degradation and provides the rationale for clinical evaluation of potent HSP90 inhibitors in genetic resistance driven by JAK2 inhibitors. Conclusion: Our study identifies JAK1 and JAK2 resistance variants against the type I JAK2 inhibitors ruxolitinib, fedratinib, and lestaurtinib. The sensitivity of these resistant variants towards the type II JAK2 inhibitor CHZ-868 indicates that this mode of type II JAK2 inhibition is a potential therapeutic approach against ruxolitinib refractory leukemia. This also proposes the development of potent and specific type II JAK2 inhibitors using ruxolitinib-resistance variants as a prototype.